Islamic banks web-marketing during the Covid-19 crisis - Tahreem Noor Khan (Indonesian Journal of Social Sciences, 2022)
Online platforms are particularly important in times of crisis, as they are a vital channel for providing and ensuring access to information. Competition increases the value of digital marketing in the banking sector; however, it also makes it more difficult to stand out in the disruption and uncertainty caused by the COVID-19 outbreak. Realizing the fact that the website has become mainstream in corporate marketing, this research investigates the practice of marketing by the largest and strongest 11 Islamic banks globally listed by the Asian Banker (2019). Information on visual elements, product features, and post locations related to corona safety precaution information was extracted from bank web pages. With that, also followed the post related to option of an opening online account and digital channel safety concern during COVID-19. Furthermore noticed on the bank webpage about the government funding for Corona activities and financial assistance to SMEs. The findings of this research suggest that in any crisis and fluid situation, where uncertainty existence is likely to be high, Islamic banks must be prepared to alter web-interface communication approaches and marketing strategies to reach their customers. To stay afloat in a highly competitive digital world, banks can advertise relevant product offerings during the Coronavirus crisis. Navigation and accessibility related to Coronavirus information on the website should be straightforward, highlight socially responsible activities, focus on customers with financial difficulty, and use differentiated and personalized banking services. Customers will regard such initiative and perceive their bank brand as compassionate, kind, and unpretentious.